Heavy metal contamination and ecological risk in sediment from typical suburban rivers - Cui, Song; Gao, Shang; Zhang, Fuxiang; Fu, Qiang; Wang, Min; Liu, Dong; Li, Kunyang; Song, Zihan; Chen, Pengyu (River research and applications, 2021)
The environmental pollution and ecological risk of riverine systems are of growing concern in China and worldwide. Previous studies have mainly focused on urban and rural rivers. However, suburban rivers differ from urban and rural rivers as they are subject to complex pollution sources, random discharge of domestic garbage, improper handling of agricultural means of production and imperfect municipal engineering facilities; thus, identifying the complex pollution sources and ecological risk in suburban rivers might help improve environmental quality and inform management decisions. The occurrence and spatial distribution of six heavy metals were investigated and analysed. The average concentrations of target heavy metals in surface sediments were in the order of Zn (1,198.7) > Cr (84.6) > Pb (40.0) > Cu (25.6) > Ni (11.8) > Cd (0.5) (mg/kg, dry weight). The concentrations of all heavy metals in the study area except Ni and Pb were significantly higher (p < .05) than the environmental background values. The pollution load index (PLI) indicated that the sediments were “moderately polluted”, which was mainly caused by Zn and Cd. The potential ecological risk index (RI) showed that there was a “high” ecological risk of heavy metals in sediments, of which Cd accounted for 83% of the RI. A principal component analysis coupled with Pearson's correlations indicated that Pb and Zn were mainly associated with domestic, traffic and agricultural sources; Cr, Cu and Ni were mainly derived from traffic and natural sources, and Cd was likely from coal combustion and agricultural sources. The results from this study will provide the scientific knowledge needed to control and manage the emissions or discharge from multiple heavy metal pollution sources and identify their potential ecological risk in the sediment of suburban rivers.